2009
DOI: 10.1677/erc-08-0127
|View full text |Cite
|
Sign up to set email alerts
|

Homeodomain transcription factor NKX2.2 functions in immature cells to control enteroendocrine differentiation and is expressed in gastrointestinal neuroendocrine tumors

Abstract: The homeodomain transcription factor NKX2.2 is necessary for neuroendocrine (NE) differentiation in the central nervous system and pancreas. NE tumors derived from the gut are defined by their NE phenotype, which is used for diagnosis and contributes to tumorigenicity. We hypothesized that NKX2.2 is important for NE differentiation in normal and neoplastic gut. NKX2.2 and NE marker expression was investigated in the small intestine of embryonic and adult mice using immunofluorescence (IF). To determine the rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
39
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 44 publications
3
39
0
Order By: Relevance
“…[4][5][6] A member of the ETS family and a marker of endothelial differentiation, FLI-1 appears less sensitive for Ewing sarcoma than CD99 and is also expressed in various other round cell tumors including neuroblastoma, lymphoma, synovial sarcoma, rhabdomyosarcoma, desmoplastic small round cell tumor, Merkel cell carcinoma, and small cell carcinoma. 7 NKX2-2, a homeodomain-containing transcription factor involved in neuronal development and glial/neuroendocrine differentiation, 8,9 is a downstream target of EWSR1-FLI1 oncogenic signaling in Ewing sarcoma. 10 In recent times, NKX2-2 has been reported as a diagnostically useful immunohistochemical marker for Ewing sarcoma.…”
mentioning
confidence: 99%
“…[4][5][6] A member of the ETS family and a marker of endothelial differentiation, FLI-1 appears less sensitive for Ewing sarcoma than CD99 and is also expressed in various other round cell tumors including neuroblastoma, lymphoma, synovial sarcoma, rhabdomyosarcoma, desmoplastic small round cell tumor, Merkel cell carcinoma, and small cell carcinoma. 7 NKX2-2, a homeodomain-containing transcription factor involved in neuronal development and glial/neuroendocrine differentiation, 8,9 is a downstream target of EWSR1-FLI1 oncogenic signaling in Ewing sarcoma. 10 In recent times, NKX2-2 has been reported as a diagnostically useful immunohistochemical marker for Ewing sarcoma.…”
mentioning
confidence: 99%
“…Wang et al carried out a series of studies to ascertain the role of NKX2.2 in normal and neoplastic gut. First, their team demonstrated the distribution of NKX2.2 expression in normal human gut tissue is similar to that in mice, supporting the use of the mouse as a model for studying NE differentiation in the human gut [26] . Then with the use of NKX2.2 mutant mice, the team evaluated NKX2.2 expression in embryonic and adult mouse proximal small intestine by immunofluorescent (IF) analysis, and gave a result that NKX2.2 expression was seen at later embryonic (E) time points and persisted in the adult intestine, which suggested that NKX2.2 is transiently expressed in immature and/or newly differentiated cells.…”
Section: Nkx22mentioning
confidence: 85%
“…Overall, the researcher detected nuclear expression of NKX2.2 in 83% (24/29) of welldifferentiated GI-NETs, including NETs of the stomach, duodenum, ampulla of Vater, pancreas, ileum, and colon. From the readily detection of intense NKX2.2 expression in most human NETs from GI sites, the conclusion were drawn that NKX2.2 is a novel NET-GI marker [26] . For more extended achievement, Wang et al selected 13 previously undescribed patients with BP-TCs identified at UCSF to ascertain whether the lack of NKX2.2 expression in BP-TCs is useful to distinguish BP-from GI-NETs, while normal human pancreas and a well-differentiated NET of pancreas and one of the ileum were used as controls.…”
Section: Nkx22mentioning
confidence: 99%
See 1 more Smart Citation
“…CDX2 is specific for GI-NETs, but it also has low and variable sensitivity and is not a good marker for pancreatic NETs (Saqi, Alexis et al 2005;Lin, Saad et al 2007;Srivastava and Hornick 2009). NKX2.2 is a highly sensitive and specific marker for GI-NETs, including NETs of the stomach, duodenum, ampulla of Vater, pancreas, ileum, and colon (Wang, Gallego-Arteche et al 2009;Wang, Iezza et al 2010). In the future, use of a panel of markers may be particularly informative (Srivastava and Hornick 2009).…”
Section: Methods For Identifying the Primary Sitementioning
confidence: 99%